Archaean andesite petrogenesis: Insights from the Grædefjord Supracrustal Belt, southern West Greenland - Szilas, Kristoffer; Hoffmann, J. Elis; Scherstén, Anders; Kokfelt, Thomas F.; Münker, Carsten (Elsevier, 2013)
We present new whole-rock major, trace and platinum-group element data, as well as Sm–Nd and Lu–Hf isotope data for meta-volcanic rocks from the Mesoarchaean Grædefjord Supracrustal Belt (GSB), located within the Tasiusarsuaq terrane, southern West Greenland. We also present new in situ zircon U–Pb isotope data (by LA-ICP-MS) for associated felsic rocks. This region has experienced amphibolite to lower granulite facies metamorphism, causing re-equilibration of most mineral phases (including zircon). An intrusive tonalite sheet with a zircon U–Pb age of 2888 ±6.8 Ma, yields a minimum age for the GSB. The Sm–Nd and Lu–Hf isotope data do not provide meaningful isochron ages, but the isotope compositions of the mafic rocks are consistent with the ca. 2970 Ma regional volcanic event, which is documented in previous studies of the Tasiusarsuaq terrane. The major and trace element data suggest a significant crustal contribution in the petrogenesis of andesitic volcanic rocks in the GSB. The trace element variation of these andesitic leucoamphibolites cannot be explained by bulk assimilation–fractional-crystallisation (AFC) processes involving local basement. Rather, the observed patterns require binary mixing between basaltic and felsic end-member magmas with between 50% and 80% contributions from the latter (depending on the assumed felsic composition). Hf-isotope constraints point to contamination with pre-existing continental crust with an age of ca. 3250 Ma. Basement gneisses of this age were previously described at two localities in the Tasiusarsuaq terrane, which supports the mixing hypothesis. Thus the felsic end-member likely represents melts derived from the local basement. Ultramafic rocks (18.35–22.80 wt.% MgO) in GSB have platinum-group element (PGE) patterns that are similar to magmas derived from high-degree melting of mantle, but they have relatively enriched trace element patterns. We propose that the ultramafic rocks represent arc-related picrites or alternatively were derived by melting of ...